A novel composite of α-MoO3/BiVO4 for triethylamine selective detection. (24th January 2020) - Bai, Shouli; Han, Jingyi; Fan, Xiangxiang; Guo, Jian; Luo, Ruixian; Li, Dianqing; Chen, Aifan
Abstract : BiVO4 modified MoO3 was synthesized by hydrothermal and metal organic decomposition. The 16Mo/Bi composite has significantly improved in the sensing properties to TEA compared with pristine MoO3, which is a hopeful sensing material for detecting TEA. Abstract : One-dimensional α-MoO3 nanorods were synthesized by a hydrothermal method and BiVO4 nanoparticles were grown directly onto the α-MoO3 nanorods using a simple metal organic decomposition process in order to construct an α-MoO3 /BiVO4 composite with a heterojunction, for the fabrication of a rapid response triethylamine (TEA) sensor. The morphology and structure of the composite were characterized via various spectral techniques and the sensing properties of the sensor for TEA were investigated via resistance measurements. The results showed that the response of the 16Mo/Bi composite to 20 ppm TEA was 1.86 times and 15 times higher than those of α-MoO3 and BiVO4, respectively, at an optimum operating temperature of 125 °C. The enhancement can be ascribed to the existence of a heterojunction between α-MoO3 and BiVO4, creating an additional barrier at the interface of the heterojunction, and this increases the resistance of the composite in air and decreases the resistance in TEA, thus enhancing the response of the composite to TEA.